Factors Related to Respiratory Infections Prevention Behaviors Lua Ethic Group Radrat Phatthana Village, Santi Suk District, Nan Province - Deesom, Kittipong; Thongprachum, Aksara; Chautrakarn, Sineenart (Princess of Naradhiwas University Journal, 2025)
Respiratory tract infections are a common cause of illness and can be prevented with appropriate preventive behaviors. This cross-sectional study aimed to investigate the factors related to respiratory infection prevention behavior among the Lua ethnic group in Radrat Phatthana village, Santi Suk District, Nan Province. The objective of this study was to examine the factors related to respiratory infection prevention behaviors among the Lua ethnic group in Radrat Phatthana village, Santi Suk District, Nan Province. The sample comprised 285 individuals using a questionnaire consisting of knowledge, attitude, and behavioral regarding respiratory infection prevention. The reliability coefficients for these sections were 0.71, 0.76, and 0.82, respectively. Data were analyzed using descriptive statistics and relationship was examined using Chi-square test statistics. The results indicated that the majority of the Lua ethnic group exhibited moderate levels of infection prevention behaviors (56.8%). Factors significantly related to respiratory infection prevention behaviors include age, occupation, working conditions involving dust, smoke, chemicals, or poorly ventilated areas, history of respiratory infections within the past year, household members’ history of respiratory infections within the past year, knowledge, and attitudes. Therefore, promoting accurate and appropriate knowledge and attitudes can help improve respiratory infection prevention behaviors among the Lua ethnic group